Color and its significance in the poetry of ibn Al-Haddad Al-Andalusi - Alsammarrie, Ban Kadhim Makki (Tanjong Malim, 2024)
Color and its significance in the poetry of ibn Al-Haddad Al-Andalusi by Alsammarrie, Ban Kadhim Makki